Development of a Portable Laser Engraving System for Small-Scale Manufacturing Applications - Herru Santosa Budiono; Sigit Joko Purnomo; Muhammad Naufal Gastiadirrijal; Wawan Setio (Universitas Negeri Jakarta, 2026)
The portable laser engraving system developed in this study integrates an APM32F103 microcontroller, external flash memory (25Q128JV), and an FSC-BT986 Bluetooth module with an Android-based engraver application. The system is designed to address limitations of bulky and costly commercial engravers by offering a compact, low-cost, and wireless alternative for educational laboratories and small-scale manufacturing. Mechanical and electronic subsystems were designed and fabricated using a knockdown frame structure and 3D-printed components. Performance evaluation included functionality testing, wireless communication stability, motion accuracy, and engraving capability on wood, MDF, acrylic, and synthetic leather. The results show stable Bluetooth communication within an effective range of 8 m, an average motion accuracy error of 0.82%, and engraving depths ranging from 0.28–0.45 mm depending on material and laser parameters. The proposed configuration demonstrates technical advantages in wireless stability, portability, and ease of use compared to conventional wired microcontroller-based laser engravers.